Rapid Lithium Diffusion in Order@Disorder Pathways for Fast‐Charging Graphite Anodes. Issue 1 (9th September 2020) - Cai, Wenlong; Yan, Chong; Yao, Yu-Xing; Xu, Lei; Xu, Rui; Jiang, Li-Li; Huang, Jia-Qi; Zhang, Qiang
Abstract : The use of graphite anode renders practical lithium‐ion batteries for effective energy storage. However, graphite anode is the bottleneck to achieve the fast charging of a battery, ascribed to its low operating potential and corresponding incidental lithium plating. Herein the principle of a thin nanoscale layer on the graphite surface to improve charging capability is investigated by applying a three‐electrode device to precisely record the working behavior. The Li + diffusion rate is significantly improved by coating a nanoscale turbostratic carbon layer, in which abundant active sites and additional fast Li + diffusion pathways at the basal‐plane side of graphite sheets render small polarization in a working battery. This fresh understanding enriches the fundamental insights into enhancing the rate performance and facilitating the practical applications of graphite in fast‐charging batteries. Abstract : The turbostratic carbon layer on the graphite anode affords abundant active sites and fast diffusion pathways to accelerate the transportation of Li ions in a working battery. This renders a reduced polarization and significantly improved rate performance.